Achievable dose reduction using iterative reconstruction for chest computed tomography: A systematic review. Issue 11 (November 2015) - den Harder, Annemarie M.; Willemink, Martin J.; de Ruiter, Quirina M.B.; Schilham, Arnold M.R.; Krestin, Gabriel P.; Leiner, Tim; de Jong, Pim A.; Budde, Ricardo P.J.
Highlights: Iterative reconstruction (IR) allows for dose reduction with maintained image quality. With IR contrast-enhanced CT at a dose below 2 mSv is possible. Non contrast-enhanced chest CT is possible at submillisievert dose using IR. Abstract: Objectives: Iterative reconstruction (IR) allows for dose reduction with maintained image quality in CT imaging. In this systematic review the reported effective dose reductions for chest CT and the effects on image quality are investigated. Methods: A systematic search in PubMed and EMBASE was performed. Primary outcome was the reported local reference and reduced effective dose and secondary outcome was the image quality with IR. Both non contrast-enhanced and enhanced studies comparing reference dose with reduced dose were included. Results: 24 studies were included. The median number of patients per study was 66 (range 23–200) with in total 1806 patients. The median reported local reference dose of contrast-enhanced chest CT with FBP was 2.6 (range 1.5–21.8) mSv. This decreased to 1.4 (range 0.4–7.3) mSv at reduced dose levels using IR. With non contrast-enhanced chest CT the dose decreased from 3.4 (range 0.7–7.8) mSv to 0.9 (range 0.1–4.5) mSv. Objective mage quality and diagnostic confidence and acceptability remained the same or improved with IR compared to FBP in most studies while data on diagnostic accuracy was limited. Conclusion: Radiation dose can be reduced to less than 2 mSv for contrast-enhanced chest CT and non contrast-enhanced chest CT is possible at a submillisievert dose using IR algorithms.